DEVELOPING CREATIVE THINKING IN SCHOOL STUDENTS THROUGH HISTORICAL ART: PEDAGOGICAL APPROACHES - Dagarova Shodiya Hayotjon qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the role of historical artworks in fostering creative thinking in school students. It examines effective pedagogical strategies for engaging learners with historical visual materials and their impact on developing imagination, critical thinking, and artistic expression. The study highlights that working with historical art enhances both cognitive and emotional skills, promoting a deeper understanding of culture and history. The findings offer practical guidance for teachers seeking to implement art-based learning methods in school curricula.